One‐Step Synthesis of Epoxy Group‐Terminated Organosilica Nanodots: A Versatile Nanoplatform for Imaging and Eliminating Multidrug‐Resistant Bacteria and Their Biofilms. Issue 37 (28th July 2019) - Chen, Xiaokai; Zhang, Xiaodong; Lin, Fengming; Guo, Yuxin; Wu, Fu‐Gen
Abstract: Multidrug‐resistant bacteria (MRB) and their biofilms, both of which develop high levels of drug tolerance, cause severe threats to global health. This study demonstrates that biocompatible fluorescent silicon‐containing nanodots can be a multifunctional platform for simultaneously imaging and eliminating MRB and their biofilms. Ultrasmall epoxy group (oxirane)‐functionalized organosilica nanodots (OSiNDs) with a high photoluminescence quantum yield of ≈31% are synthesized via a simple one‐step hydrothermal treatment of an epoxy group‐containing silane molecule, 3‐glycidoxypropyltrimethoxysilane, and an organic dye, rose bengal. The resultant OSiNDs can be employed as a universal imaging reagent for visualizing various bacteria/biofilms, including MRB and their biofilms. Moreover, the epoxy group‐terminated OSiNDs can be conjugated with amine‐containing reagents only via the simple stirring of the mixtures at an elevated temperature (e.g., 60 °C) for several hours (e.g., 3 h) without the addition of activating reagents. The amine‐containing antibiotic vancomycin (Van) can thus be easily conjugated with the OSiNDs, and the obtained OSiNDs‐Van can successfully inhibit the growth of MRB and even eliminate their biofilms. Collectively, the present work may give new impetus to the development of novel antibacterial and anti‐biofilm agents for overcoming the drug resistance of bacteria. Abstract : A new type of water‐dispersible organosilica nanodots terminated with epoxy groups are synthesized and adopted as a versatile nanoplatform for imaging various bacteria and biofilms. After conjugation with the amine‐containing antibiotic vancomycin, the obtained vancomycin‐loaded nanodots can effectively inhibit the growth of multidrug‐resistant bacteria and even eliminate their biofilms.